2019
DOI: 10.3892/mmr.2019.10073
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of microRNAs in rats following focal cerebral ischemia injury

Abstract: MicroRNA sequencing (miRNA-seq) was performed in the present study to investigate miRNA expression profiles in infarcted brain areas following focal cerebral ischemia induced by middle cerebral artery occlusion in rats. In total, 20 miRNAs were identified to be upregulated and 17 to be downregulated in the infarct area. The expression levels of six differentially expressed miRNAs (DEmiRs), miR-211-5p, miR-183-5p, miR-10b-3p, miR-182, miR-217-5p and miR-96-5p, were examined by reverse transcription-quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Through using starBase software, we predicted the candidate miRNA targets of GAS5. Among all these predicted targets, six miRNAs were screened out due to their vital roles in regulating cerebral ischemia-reperfusion injury, including miR-34b-3p, 13 miR-485-3p, 16 miR-211-5p, 17 miR-217-5p, 18 miR-874-3p 19 and miR-338-5p. 20 We tested the regulatory relationships between GAS5 and these candidate targets.…”
Section: Resultsmentioning
confidence: 99%
“…Through using starBase software, we predicted the candidate miRNA targets of GAS5. Among all these predicted targets, six miRNAs were screened out due to their vital roles in regulating cerebral ischemia-reperfusion injury, including miR-34b-3p, 13 miR-485-3p, 16 miR-211-5p, 17 miR-217-5p, 18 miR-874-3p 19 and miR-338-5p. 20 We tested the regulatory relationships between GAS5 and these candidate targets.…”
Section: Resultsmentioning
confidence: 99%
“…miR-6328 was identified as a rat-specific miRNA derived from intronic regions of chromosome 20 and its functions are unknown ( Clokie et al, 2012 ). On the other hand, the expression of miR-10b-3p , conserved across rodents and humans, is increased in rat brains undergoing stress-induced depression or decreased in rats exposed to cold stress and in regions of brain damage following ischemia ( Zhen et al, 2017 ; Duan et al, 2019 ; Fang et al, 2020 ). Even though no link between miR-10b-3p and epilepsy has been established so far, the 5p strand of miR-10b is linked to epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the miR-183 gene cluster, the normal expression of miR-183-5p is important for nervous system function ( 30 ). A previous study has revealed that 17 miRNAs, including miR-183-5p, were downregulated in infarcted brain areas following focal cerebral ischemia in rats according to microRNA sequencing compared with healthy tissues ( 31 ). The results of the present study demonstrated decreased levels of miR-183-5p in MCAO models of cerebral ischemia injury and OGD-treated N2A cells compared with those in the respective control groups.…”
Section: Discussionmentioning
confidence: 99%